Responses of Functional and Taxonomic Phytoplankton Diversity to Environmental Gradients in Subtropical and Tropical Reservoirs - Santos, Juliana B. O.; Brasil, Jandeson; Huszar, Vera L. M. (Frontiers in Environmental Science, 2022)
Understanding the influence of environmental conditions on biodiversity is a major task in ecology. We investigated how phytoplankton taxonomic (TD) and functional (FD) diversities vary with environmental factors in eight subtropical and tropical reservoirs. We hypothesized that i) environmental variables affect phytoplankton TD and FD; ii) FD provides better relationships to environmental changes than TD, and; iii) indices based on biomass are better related to the environment than those based on identities. The relationships between phytoplankton diversities and environmental drivers were assessed through generalized linear models. Our hypotheses were partly confirmed. TD and FD were, in fact, dependent on the environment, with higher values occurring in warmer, clearer, and more enriched systems, under lower zooplankton grazing pressure; but FD based on identities was not predicted better from environmental conditions than TD based on identities. As expected, indices based on biomass are better related to the environment than their counterpart based on identities.